Determining the optimal threshold for medication adherence in adult asthma patients: an analysis of British Columbia administrative health database in Canada. (10th November 2022) - Asamoah-Boaheng, Michael; Farrell, Jamie; Osei Bonsu, Kwadwo; Midodzi,, William K.
Abstract: Objective: This study investigated the association between varying cutoffs for Medication Adherence (MA) among physician-diagnosed asthma patients and subsequent association with asthma exacerbation. Methods: We linked four administrative health databases obtained from the Population Data in British Columbia. Index cases were physician-diagnosed asthma patients between January 1, 1998, to December 31, 1999, aged 18 years and older. Patients were prospectively assessed in the follow-up period from January 1, 2000, to December 31, 2018, to identify asthma exacerbation. Two proxy measures were used to assess MA: the proportion of days covered (PDC) and the medication possession ratio (MPR). Using the generalized estimating equation (GEE) logistic regression adjusted for patient covariates, the outcome of "asthma exacerbation" was modeled against varying MA cutoffs; excellent '≥0.90'; very good '0.80–0.89'; good '0.70–0.799'; moderate '0.6–0.699'; mild '0.50–0.599' compared to poor '<0.50' for both PDC and MPR. Results: The sample included 68, 211 physician-diagnosed asthma patients with a mean age of 48.2 years and 59.3% females. The adjusted odds ratios (OR) and 95% confidence interval (CI) at the various cutoff for PDC-levels predicting asthma exacerbation events were: Excellent MA [OR = 0.84, 95% (0.82–0.86), very good MA [OR: 0.86, (0.83, 0.89), good MA [0.91, (0.88–0.94)]; moderate MA [0.93, (0.90–0.96)]; mild MA [0.95, (0.92–0.98)]; compared to poor MA level. Threshold levels for both the PDC and MPR measure greater than 0.80 provided optimal threshold associated with over 15% reduced likelihood of experiencing asthma exacerbations. Conclusion: Intervention aimed at improving asthma exacerbation events in adult asthma patients should encourage increased medication adherence threshold level greater than 0.80. Supplemental data for this article is available online at at www.tandfonline.com/ijas .